Review and Bibliometric Analysis of Research on Self-Medication Since Year 2000 - Mora Gómez, Érika Marcela (2018)
Self-medication is a transcultural practice which includes populations of all ages. Said practice focus on the vaguest conception of people’s self-care or biological well-being preservation, illness prevention, and health promotion. However, self-medication can be as harmful as not treating the conditions that threaten health. This situation results in raising questions in the scientific field. The present article aims at presenting the set of variables regarding self-medication that have been most frequently studied in scientific literature since year 2000 until now. Two different conclusions arise from this bibliometric analysis: to confirm the global establishment of self-medication phenomenon, and to find out the constant trend of variables linked to this high-risk behavior.